Alarm device for locating people submerged beneath water based on the geomagnetic sensor. (2018) - Zhou, Chen; Lin, Liu; Wang, Quan
An alarm device consisting of data collection module, control module and radio frequency module for locating people submerged beneath water is investigated. By combining the magnetic field distribution information and acceleration sensor, the alarm device is able to simulate submerged person movement path in the data collection module. STC89C51 is selected as the main control chip in the control module for alarm switching, information encoding and control of radio frequency mode. A third-generation wireless transceiver chip nRF2401 is adopted in the radio frequency module, allowing data transmission in the international ISM frequency range. The implementation based on the geomagnetic sensor that is simple in design, boasts full functions and has excellent drowning detection sensitivity. Additional wireless emission coordinate capability will improve efficiency and shipwreck rescue and maritime navigation in the future.